The Effect of Constructive Alignment in Course Design on Accounting Students’ Development of Written Communication Competence - Irafahmi, Diana Tien; Williams, P John; Lim, Nena (Universitas Negeri Malang, 2022)
The purpose of this study was to examine the effects of Constructive Alignment (CA), that is aligning learning outcomes, learning activities and assessment tasks, on students’ development of competence in written communication. A counterbalancing two-phase experimental design was adopted. Third-year undergraduate accounting students in an advanced auditing course were randomly assigned into two groups. In phase 1, Group 1 received the constructive alignment intervention, and Group 2 studied in a traditional learning situation. In phase 2, the order of intervention was reverse, where Group 2 received the intervention, and Group 1 did not receive the intervention. Participants’ written competency was measured before and after each phase by using an auditing writing test. Qualitative comments were also collected in group interviews. The study found that in the phase when students received constructive alignment intervention, they write better than the students who did not receive constructive alignment intervention. This finding indicates that constructively aligning learning outcomes, learning activities, and assessment tasks around writing help improve accounting students’ written communication competence. For decades, accounting practitioners and employers have been lamenting over the inadequacy of accounting students’ written communication competence. Results of this study provide useful and positive evidence to accounting educators on the importance of aligning components in course design to develop students’ communication competence as required by the profession. Educators who intend to develop students’ competence in written communication can be encouraged to redesign their courses according to the constructive alignment framework.